The Effect of Work-Family Conflict, Organizational Citizenship Behavior, And Job Placement on Job Satisfaction Among Employees at BKPSDM Badung Regency - Kartini, Kadek Ayu; Aristana, I Nengah; Puspitawati, Ni Made Dwi (EMAS: Jurnal Ekonomi, Manajemen dan Bisnis, 2026)
This study aims to analyze the effect of work-family conflict, organizational citizenship behavior, and job placement on employee job satisfaction at BKPSDM Badung Regency. This study is quantitative in nature. The population in this study consists of all 87 employees of BKPSDM Badung Regency. The sampling technique used is the saturated sample technique, where the selection in this study uses the entire population. The data analysis technique used in this study was Multiple Linear Regression Analysis. The results showed that work-family conflict had a negative and significant effect on job satisfaction at BKPSDM Badung Regency. This means that a decrease in work-family conflict in the work environment of BKPSDM Badung Regency employees can have a positive impact on increasing job satisfaction. Organizational citizenship behavior has a positive and significant effect on job satisfaction at BKPSDM Badung Regency. This means that the better the organizational citizenship behavior of each employee, the more positive the impact on increasing job satisfaction at BKPSDM Badung Regency. Job placement has a positive and significant effect on job satisfaction at BKPSDM Badung Regency. This means that the more appropriate the job placement of employees implemented by the Badung Regency BKPSDM, the more positive the impact on increasing job satisfaction. The researcher suggests that future researchers should add other variables such as internal control, compensation, competence, and others. In addition, it is necessary to increase the number of samples and expand the scope of the research beyond the Badung Regency BKPSDM.